Close Campus Friendships and College Student Success. (November 2019) - Bronkema, Ryan H.; Bowman, Nicholas A.
Friendships are widely considered to be an essential part of life in college and beyond. The existing literature on college friendships, academic achievement, and student attrition is mixed, which may occur as a result of varying ways of defining friendship. This study adds to an understanding of these dynamics by examining both the number of close campus friends as well as the emotional connection students have with these friends within a large, multi-institutional sample. Multilevel analyses found that both of these attributes of campus friendships are positively and significantly related to six-year graduation rate, whereas only the number of close campus friends significantly predicts college grade point average.